Factors influencing fuel retail site sales in South Africa pre- and post-COVID-19 - Kader, Junaid Abdul (University of the Witwatersrand, Johannesburg, 2022)
The association between the volume of fuel sold at retail sites and predictor variables has been explored in prior research. The COVID-19 pandemic was at its height in South Africa between March 2020 and March 2022 and might have changed these associations due to restrictions on people’s movements and lifestyles during the peak of the pandemic. Understanding changes in the retail fuel industry might help Government, together with the private sector, to ensure adequate fuel supply through efficient utilisation of resources. Therefore, the association between the volume of fuel sold at retail sites and predictor variables in South Africa before and after COVID-19 was explored through this quantitative study using regression analysis and Fisher transformations. It was hypothesised that the volume of fuel sold at retail sites in South Africa was associated with the average income per adult residing within two kilometres of the fuel retail site, adult population residing within two kilometres of the fuel retail site, car ownership by people residing within two kilometres of the fuel retail site, number of competitor sites within two kilometres of the fuel retail site, saturation level, location metric, and site services. In addition, it was hypothesised that the associations did not change between 2020 and 2022. Regression analysis showed that saturation level and site services had a statistically significant association, albeit with a low R-square, with the volume of fuel sold at retail sites, while the other variables did not have a statistically significant association. In addition, Fisher transformations showed that the associations did not change between 2020 and 2022. Perhaps, there was insufficient differentiation between fuel retail competitors in South Africa to influence consumer choice. Fuel could also be regarded as a commodity by consumers and their needs were equally served at any retail site.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in Energy Leadership Johannesburg, 2022
Keywords: COVID-19; Fuel sales; Fuel retail sites; South Africa; Quantitative regression; UCTD; SDG-8: Decent work and economic growth